'Korea … it's not really actually an Asian country': Australian children's experiences of an intercultural school partnership programme. Issue 3 (3rd July 2019) - Walton, Jessica
ABSTRACT: In Australia, intercultural understanding has been prioritised in education and curriculum documents at both federal and state levels. Alongside this educational priority, schools have also been encouraged to demonstrate 'engagement' with 'Asia', such as through a partnership with another school in the Asia-Pacific region. My research findings are based on an ethnographic study of Year 5 and 6 Australian children's experiences of an intercultural school partnership initiative through on-line classroom exchanges over a two-year period. Through a critical analysis of 'complexity reduction' I draw attention to the processes through which children made sense of perceived racial and cultural differences as part of their involvement in partnership activities and conclude with some reflections on the extent to which educational initiatives such as intercultural school partnership programmes that aim to foster intercultural understanding can do so without reinforcing unequal intercultural relations and stereotypes.